1994
DOI: 10.1073/pnas.91.8.3132
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and analysis of the breakpoint sequences of chromosome inversion In(3L)Payne in Drosophila melanogaster.

Abstract: Chromosomal rearrangements constitute a significant feature of genome evolution, and inversion polymorphisms in Drosophila have been studied intensely for decades. Population geneticists have long recognized that the sequence features associated with inversion breakpoints would reveal much about the mutational origin, uniqueness, and genealogical history of individual inversion polymorphisms, but the cloning of breakpoint sequences is not trivial. With the aid of a method for rapid recovery of DNA clones sanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
94
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(98 citation statements)
references
References 17 publications
4
94
0
Order By: Relevance
“…The break in the chromosome may result in a fortuitous selective advantage, either by disrupting a gene where the breakpoint occurs or by changing gene expression in the chromosomal neighborhood. This kind of ''position effect'' has been documented in the inversion In(3L)Payne in Drosophila (Wesley and Eanes 1994). On the other hand, the results from searches for gene disruption caused by the inversions that distinguish humans and chimps have to date been negative (Kehrer-Sawatzki et al 2002, 2005.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The break in the chromosome may result in a fortuitous selective advantage, either by disrupting a gene where the breakpoint occurs or by changing gene expression in the chromosomal neighborhood. This kind of ''position effect'' has been documented in the inversion In(3L)Payne in Drosophila (Wesley and Eanes 1994). On the other hand, the results from searches for gene disruption caused by the inversions that distinguish humans and chimps have to date been negative (Kehrer-Sawatzki et al 2002, 2005.…”
Section: Discussionmentioning
confidence: 98%
“…It is thus plausible that the inversion affects patterns of gene expression, a result known from other inversions (Wesley and Eanes 1994). A survey of polymorphism in the vicinity of the breakpoint shows a pattern reminiscent of Adh: it appears that one or more sites have been under balancing selection for much longer than the age of the inversion and further that haplotype frequencies vary geographically (Andolfatto and Kreitman 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The transposable-element model proposed that these repetitive sequences act as sites for ectopic exchange within chromosomal arms, leading to rearrangement. Sequences at inversion breakpoints have (Mathiopoulos and Lanzaro 1995;Mathiopoulos et al 1998Mathiopoulos et al , 1999Cáceres et al 1999Cáceres et al , 2001) and have not found repetitive sequences at the breakpoints of gene arrangements (Wesley and Eanes 1994;Andolfatto and Kreitman 2000;Anderson et al 2005;Matzkin et al 2005). Several studies of rearrangement breakpoints have shown that the gene duplications often accompany the rearrangement event (Matzkin et al 2005;Ranz et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, extant sequences of polymorphic inversion breakpoints are expected to better reflect the sequences in the original inverted chromosome. Despite the extensive knowledge accumulated on inversion polymorphism in Drosophila, there are relatively few polymorphic inversion breakpoints molecularly characterized both in any particular species and across species (but see Wesley and Eanes, 1994;Andolfatto et al, 1999;Cáceres et al, 1999;Casals et al, 2003;Matzkin et al, 2005;Richards et al, 2005;Delprat et al, 2009;Papaceit et al, 2013;Puerma et al, 2014). The number of molecularly characterized breakpoints drops even more when inversions with cytological evidence of reused breakpoints are considered Puerma et al, 2014).…”
Section: Introductionmentioning
confidence: 99%